Sexuality : the 1964 Clermont-Ferrand and 1969 Vincennes lectures - Foucault, Michel, 1926-1984 (Columbia University Press, 2021)
"Michel Foucault's The History of Sexuality-the first volume of which was published in 1976-exerts a vast influence across the humanities and social sciences. However, Foucault's interest in the history of sexuality began as early as the 1960s, when he taught two courses on the subject. These lectures offer crucial insight into the development of Foucault's thought yet have remained unpublished until recently. This book presents Foucault's lectures on sexuality for the first time in English. In the first series, held at the University of Clermont-Ferrand in 1964, Foucault asks how sexuality comes to be constituted as a scientific body of knowledge within Western culture and why it derived from the analysis of "perversions"-morbidity, homosexuality, fetishism. The subsequent course, held at the experimental university at Vincennes in 1969, shows how Foucault's theories were reoriented by the events of May 1968; he refocuses on the regulatory nature of the discourse of sexuality and how it serves economic, social, and political ends. Examining creators of political and literary utopias in the nineteenth and twentieth centuries, from Sade to Fourier to Marcuse, who attempted to integrate "natural" sexualities, including transgressive forms, into social and economic life, Foucault elaborates a double critique of the naturalization and the liberation of sexuality. Together, the lectures span a range of interests, from abnormality to heterotopias to ideology, and they offer an unprecedented glimpse into the evolution of Foucault's transformative thinking on sexuality"--